Proteomic Analysis on Anti-Proliferative and Apoptosis Effects of Curcumin Analog, 1,5-bis(4-Hydroxy-3-Methyoxyphenyl)-1,4-Pentadiene-3-One-Treated Human Glioblastoma and Neuroblastoma Cells - Lee, Yee Qian; Rajadurai, Pathmanathan; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (Frontiers in Molecular Biosciences, 2021)
Curcumin analogues with excellent biological properties have been synthesized to address and overcome the poor pharmacokinetic profiles of curcumin. This study aims to investigate the cytotoxicity, anti-proliferative and apoptosis-inducing ability of curcumin analogue, MS13 on human glioblastoma U-87 MG and neuroblastoma SH-SY5Y cells, and to examine the global proteome changes in these cells following treatment. Our current findings showed that MS13 induced potent cytotoxicity and anti-proliferative effects on both cells. Increased caspase-3 activity and decreased bcl-2 concentration upon treatment indicate MS13 induces apoptosis in these cells in dose- and time-dependent manner. A label-free shotgun proteomic analysis was performed to reveal global proteome changes in both glioblastoma and neuroblastoma cells and further underpin the underlying anti-cancer mechanism of MS13. Results showed that a total of nine common DEPs, inclusive of GAPDH, ENO1, HSP90AA1, HSP90AB1, EFI5A, HNRNPK, TUBB, H2AFX and SET were identified. Pathway analysis further elucidated that MS13 may induce its anti-tumor effects in both cells via the common enriched pathways, “Glycolysis” and “Post-translational protein modification”. In conclusion, the underlying mechanism of action of MS13 demonstrates potent anti-cancer effects that may indicate potential therapeutic intervention in the management of brain malignancies.